2006
DOI: 10.1213/01.ane.0000202395.94542.3e
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of Opioid Weaning in Opioid-Dependent Pediatric Critical Care Patients

Abstract: Critically ill children are treated with opioid medication in an attempt to decrease stress and alleviate pain during prolonged pediatric intensive care. This treatment plan places children at risk for opioid dependency. Once dependent, children need to be weaned or risk development of a withdrawal syndrome on abrupt cessation of medication. We enrolled opioid-dependent children into a prospective, randomized trial of 5- versus 10-day opioid weaning using oral methadone. Children exposed to opioids for an aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
104
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 17 publications
0
104
0
Order By: Relevance
“…Nine of the patients had been started on clonidine during the phase of nonstandardized opioid weaning in unsuccessful attempts to prevent withdrawal. A subsequent randomized double-blind follow-up study by the same group of investigators 151 found that in a group of 37 fentanyltreated patients, a 5-day methadone taper was as successful as the longer 10-day course (13 of 16 vs 17 of 21 [not significant]) in discontinuing opioid infusions without causing withdrawal. In contrast to their previous study, a standardized taper of lorazepam was allowed in 17 of the 37 patients while on the methadone protocol.…”
Section: Management Of Acquired Opioid and Benzodiazepine Dependencymentioning
confidence: 99%
See 1 more Smart Citation
“…Nine of the patients had been started on clonidine during the phase of nonstandardized opioid weaning in unsuccessful attempts to prevent withdrawal. A subsequent randomized double-blind follow-up study by the same group of investigators 151 found that in a group of 37 fentanyltreated patients, a 5-day methadone taper was as successful as the longer 10-day course (13 of 16 vs 17 of 21 [not significant]) in discontinuing opioid infusions without causing withdrawal. In contrast to their previous study, a standardized taper of lorazepam was allowed in 17 of the 37 patients while on the methadone protocol.…”
Section: Management Of Acquired Opioid and Benzodiazepine Dependencymentioning
confidence: 99%
“…Hence, current instruments will not reliably differentiate whether withdrawal symptoms stem from relative opioid or benzodiazepine abstinence. 153 Other scales have been proposed for children and are in various stages of evaluation, including the Opioid and Benzodiazepine Withdrawal Scale, 151 the Sedation Withdrawal Score, 154 and the Sophia Benzodiazepine and Opioid Withdrawal Checklist. 155 At this time, no optimal pharmacologic regimen for the prevention or treatment of acquired opioid and/or benzodiazepine dependency can be recommended, because the necessary comparative studies of safety and efficacy are not available.…”
Section: Management Of Acquired Opioid and Benzodiazepine Dependencymentioning
confidence: 99%
“…3 Fetal exposure usually occurs for 1 of 3 reasons: (1) mothers are addicted to opioids, either prescribed or illicit; (2) mothers require prescription opioids for another disease process; or (3) mothers receive methadone therapy or other agents to facilitate safe withdrawal from addiction to prescription or illicit opioids. 4 Cord clamping, the catalyst necessary to initiate the cascade of events, causes the abrupt withdrawal of the substance to the infant.…”
mentioning
confidence: 99%
“…Articles on withdrawal symptoms had to meet two criteria for inclusion in this review: describing a study of benzodiazepine and/or opioid withdrawal symptoms and relating to the age restriction. In total 20 articles, either case studies, retrospective or prospective studies, met these criteria [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Table 1 lists the studies from which the withdrawal symptoms were derived, grouped by type of medication, study design, and methodological quality.…”
Section: Methodsmentioning
confidence: 99%